Decomposing movements in U.S. non-energy import market shares - Russell Barnett; Karyne Charbonneau (Bank of Canada, 2015)
Country market shares of U.S. non-energy imports have changed considerably since 2002, with varying volatility across three subperiods: pre-crisis (2002-07), crisis (2007-09) and post-crisis (2009-14). In this paper, we analyze market shares for four main trading partners of the United States (Canada, Mexico, China and Japan). We use shift-share analysis to decompose movements in the aggregate market shares into those related to actual shifts in product-specific market shares, versus shifts in the composition of U.S. import demand and the interaction between these two effects. Our analysis shows that separating these effects is important, since shifts in product-specific market shares explain varying amounts of movements in the overall market shares across countries and between time periods. Specifically, we find that two-thirds of Canada's decline in U.S. market share is due to shifts in product-specific market shares and that these losses were relatively stable across subperiods. In contrast, losses associated with a shift in the composition of U.S. import demand were most important during the crisis and have in fact supported Canada's market share since 2009. We also find that almost three-quarters of Canada's total loss in market share was concentrated in two sectors: (i) motor vehicles and parts, and (ii) forestry products and building and packaging materials. Japan's loss in U.S. market share was very similar to Canada's over this period. In contrast, China and Mexico both gained market share between 2002 and 2014. China gained mostly in product-specific market share, while Mexico benefited from favourable shifts in U.S. import demand. – – Les parts de marché aux États-Unis des pays exportateurs de produits non énergétiques ont beaucoup évolué depuis 2002, affichant une volatilité variable au cours de trois sous-périodes : avant-crise (2002-2007), crise (2007-2009) et après-crise (2009-2014). Dans cette étude, les auteurs analysent les parts de marché de quatre des principaux partenaires commerciaux des États-Unis (Canada, Mexique, Chine et Japon). Au moyen d'une analyse structurelle résiduelle, ils décomposent les variations des parts de marché globales en trois effets : variations liées aux modifications réelles des parts de marché des divers produits, modifications de la composition de la demande américaine d'importations et interaction entre ces deux effets. Leur analyse montre qu'il est important de séparer ces effets, car les modifications des parts de marché selon les produits expliquent une portion variable des mouvements de l'ensemble des parts de marché entre les pays et entre les périodes. Plus précisément, les auteurs constatent que les deux tiers du recul de la part du marché américain des exportations canadiennes sont attribuables à des modifications des parts de marché des divers produits et que ces pertes étaient relativement stables tout au long des sous-périodes. En revanche, les pertes associées à une modification de la composition de la demande américaine d'importations ont été les plus importantes durant la crise et ont, dans les faits, appuyé les parts de marché du Canada depuis 2009. Les auteurs observent également que presque les trois quarts de la perte totale de parts de marché du Canada étaient concentrés dans deux secteurs : 1) les véhicules et pièces automobiles et 2) les produits forestiers ainsi que les matériaux de construction et d'emballage. Le recul des parts de marché des exportations japonaises vers les États-Unis a été très similaire à celui enregistré par le Canada au cours de la même période. À l'inverse, les parts de marché de la Chine et du Mexique ont progressé entre 2002 et 2014. La Chine a vu croître principalement les parts de marché de ses divers produits, tandis que le Mexique a profité de modifications favorables de la demande américaine d'importations.
Keywords: F4; F10; F14; 330; International topics; Questions internationales